Cost Pass Through Analysis: A Case Study on Oil Prices in Indonesia - Dede Ruslan; Annisa Handayani; Rinaldi Rinaldi; Tegar Efrahim Gilbert Siahaan; Yan Septian (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This study aims to analyze the relationship between changes in world crude oil prices and gasoline prices in Indonesia in the period 2000–2024. Using a quantitative approach and descriptive method, this study utilizes secondary data from Trading Economics to measure the elasticity and cost pass-through rate between the two variables. The results of the study indicate that gasoline prices in Indonesia do not always follow changes in world crude oil prices directly. This is due to government policies, such as subsidies and price controls, which are designed to maintain people's purchasing power and reduce the impact of inflation. The low value of the elasticity of gasoline prices to world crude oil shows the significant role of government intervention in regulating fuel prices. Compared to countries without significant intervention, such as the United States, fuel prices in Indonesia tend to be less elastic to the decline in world oil. This study also highlights the impact of subsidies on domestic economic stability, although subsidies impose a long-term burden on the state budget. This study offers important insights for policymakers to design a balanced strategy in maintaining domestic price stability while reducing the burden of subsidies, so that the impact of world oil prices on the Indonesian economy can be minimized.